MEDIA ALTERNATIF PERTUMBUHAN Staphylococcus aureus DARI BIJI DURIAN (Durio Zibethinus murr) - Siti Juariah (Meditory : The Journal of Medical Laboratory, 2021)
Media that is often used for bacterial growth is Nutrient agar. The high price incurred for the manufacture of instant media becomes a constraint so that innovation is needed that can reduce the cost of expenditure that is looking for alternative media from materials that are easily available. One of the natural ingredients that have a source of nutrients that can be used for bacterial growth of durian seeds that have a high carbohydrate content as a source of carbon. The objective of this research was to know the growth of Staphylococcus aureus bacteria on alternative medium of durian seed as substitution media of Nutrient agar. This research is laboratory experimental research, the sample used is durian seed with three concentrations of 200 g, 300 g, 400 g. The parameters observed were calculating total plate number and morphological form of Staphylococcus aureus bacteria growth. The results showed that the highest population on medium durian medium was the concentration of 200 g as much as 5.7 x 10-4 cfu and the lowest population at the concentration of 400 g was 3.5 x 10-3 cfu. While the population on the media Nutrient agar that is 7.7 x 10-6 cfu. Based on morphological observation of bacterial growth on durian seed medium, round shape, size 0.1 cm, white milk color, smooth surface, and convex elevation. The conclusion of this research is the growth of Staphylococcus aureus on alternative medium of durian seeds can be used as substitution media of Nutrient agar.